Efeito do fulerol nas alterações inflamatórias associadas à mucosite e isquemia e reperfusão intestinal em camundongos - Raquel Duque do Nascimento (2011)
The incidence of intestinal inflammation has increased in the last decades, especially in Western countries. Various stimuli may lead to this process, although the resulting inflammation usually converges to a final common pathway, characterized by excessive T cell activation, neutrophil infiltration and increased production of cytokines and ROS. Taking into account that ROS participate in the intestinal inflammatory cascade, considerable attention has been given to the use of antioxidants as an approach to control intestinal inflammation. In this context, we analyzed the fullerol (a nanocomposite with antioxidant properties) as a therapeutic strategy in two models: Irinotecan-induced mucositis and intestinal ischemia-reperfusion injury (IRI) induced by occlusion of the superior mesenteric artery. Mucositis is a toxic response associated with chemotherapic use and is characterized by intense inflammatory process. The intestinal ischemia and reperfusion is a severe abdominal emergency and restoration of blood supply is therapeutic option to replenish bowel function after ischemia. However the reperfusion results in intense inflammatory response. The fullerol protected against neutropenia, attenuated weight loss and intestine shortening and decreased tissue damage in the mucositis model. This improvement was associated with decreased neutrophils and eosinophil influx, maintenance of GSH and catalase levels and decreased IL-1 production. In the IRI model, fullerol decreased neutrophil number in blood and in intestine, reduced vascular permeability, tissue damage and delayed mortality. This improvement was associated with diminished concentrations of CXCL-1 and, consequently, lower neutrophil influx, resulting in a less intense inflammatory process with reduction of proinflammatory cytokines, especially TNF-. These results led us to conclude that fullerol exerts anti-inflammatory activity in mucositis and IRI models.